PENGARUH KOMITE AUDIT TERHADAP CORPORATE SOCIAL RESPONSIBILITY MELALUI KEBERADAAN MANAJEMEN RISIKO - Irena Ghina Nazibah Nasution; Andrian Budi Prasetyo (Diponegoro Journal of Accounting, 2022)
This purpose of this study was to examine the effect of the audit committee on the disclosure of corporate social responsibility with the presence of risk management as a mediating variable. The audit committee is proxied by size, independence, meetings and financial expertise. The population used in this study are non-financial companies listed on the Indonesia Stock Exchange in 2016-2018. This study uses purposive sampling method with a total sample of 46 companies. The data used in this study uses secondary data taken from the annual reports and sustainability report of non financial companies. Multiple linerar regression was used as the analytical method. The results of the analysis show that the independence of the audit committee, the audit committee meeting has an indirect and not have a significant effect on the disclosure of corporate social responsibility which is mediated by risk management, and the audit committee’s financial expertise and the size of the audit committee has an indirect and not have a significant effect on the disclosure of corporate social responsibility mediated by risk management.